Post penetrating keratoplasty infectious keratitis: Clinico-microbiological profile and predictors of outcome. Issue 5 (September 2022) - Dave, Abhishek; Sawant, Sanil; Acharya, Manisha; Gandhi, Arpan; Majumdar, Atanu; Mathur, Umang
Purpose: To study the clinico-microbiological profile, outcomes and prognostic factors of post penetrating keratoplasty (PKP) infectious keratitis. Methods: Retrospective review of medical records of 78 patients with post PKP infectious keratitis presenting between January 2014 and December 2018. Demographic, clinical and microbiological profile was documented and predictors of treatment and graft success were evaluated using univariate and subsequent multivariate logistic regression analysis. Results: Mean age of patients was 52.17 ± 15.51 years and mean infiltrate size was 19.39 ± 19.68 mm 2 . Mean duration of presentation with infection post PKP was 11.66 ± 10.65 months. Culture positivity was seen in 64 eyes (82.05%). Bacterial growth was observed in 47 eyes (60.25%), fungal growth in 17 (21.79%) and no microbiological growth in 14 eyes (17.94%). At 3 months the visual acuity (VA) improved in 37 eyes (47.44%), did not change in 27 (34.62%) and deteriorated in 14 (17.95%). Graft failure was noted in 53 eyes (73.08%). Surgical intervention was needed in 47 (60.25%) eyes of which most common was therapeutic PKP in 32 eyes (41.02%). Treatment failure was noted with fungal infection ( p = 0.05), poorer vision at presentation ( p = 0.02), larger infiltrate area ( p = 0.002) and graft infection developing before 1 year ( p = 0.02). Graft failure was noted with associated endophthalmitis ( p = 0.02), poorer VA at presentation ( p = 0.01) and larger infiltrate area ( p = 0.02). Conclusion: Post PKP infectious keratitis is a sight threatening ocular condition. It is associated with high incidence of graft failure and frequently requires surgical intervention. Fungal etiology, larger infiltrate size, poorer vision at presentation and associated endophthalmitis carries a poorer prognosis.